From the Debt Crisis toward Economic Stability : An Analysis of the Consistency of Macroeconomic Policies in Mexico - Rojas-Suarez, Liliana (IMF Working Papers; Working Paper, 1992)
This paper uses a simple framework based on the government budget constraint to analyze the consistency of macroeconomic policies undertaken in Mexico during the period 1978 to mid-1991. It was found that the interaction between the actual implementation of economic policies and economic agents' perceptions about the sustain-ability of those policies can account, to a large extent, for the behavior of key macroeconomic variables during the period under study. The paper also highlights the costs of adjustment involved in the most recent Mexican stabilization program arising from concerns about the sustainability of the announced policies.